Sealing agent for dye-sensitized solar cells and dye-sensitized solar cells using the same
Patent Information
- Application Number
- JP2023148841
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-27
AI Technical Summary
【0012】 本発明によれば、作製した色素増感太陽電池セルにおいて電解液封止性能に優れ、セルの耐久性を向上させることができる色素増感太陽電池用シール剤を提供することができる。
Smart Images

Figure 2025042049000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a sealant for dye-sensitized solar cells and a dye-sensitized solar cell using the same, and more particularly to a sealant for dye-sensitized solar cells that utilizes ultraviolet curing and / or thermal curing and a dye-sensitized solar cell using the same. [Background technology]
[0002] Solar cells, which have been attracting attention as a clean energy source, have recently begun to be used in ordinary homes. However, they have not yet become widespread. The reasons for this include the fact that the performance of solar cell elements is not sufficiently excellent, so modules have to be large, and that the productivity of module manufacturing is low, making them expensive.
[0003] There are several types of solar cells, but the majority of solar cells in practical use are silicon solar cells. However, dye-sensitized solar cells have recently been attracting attention and are being studied with the aim of practical use. The prototype of the current dye-sensitized solar cell was developed by Graetzel (Switzerland) et al. in 1991, and is also called the Graetzel cell. Its structure generally consists of a conductive support (oxide semiconductor electrode) having a layer of oxide semiconductor particles sensitized by a dye, a second conductive support having a counter electrode such as platinum as a counter electrode, a charge transfer layer (electrolyte solution containing a redox substance, etc.) sandwiched between the two electrodes, and a sealant such as a resin arranged around the charge transfer layer. In addition, the performance of the solar cell has reached a level where it has a photoelectric conversion efficiency comparable to that of an amorphous silicon solar cell, for example, by adsorbing a ruthenium complex dye to a porous titanium oxide electrode (Non-Patent Document 1). However, there are still many challenges to be overcome before it can be put into practical use, and improving the productivity to accommodate larger battery areas and improving durability for long-term use are important challenges to be overcome.
[0004] In general, dye-sensitized solar cells are manufactured by providing a predetermined gap between an oxide semiconductor electrode and a counter electrode, bonding the electrodes together with a sealant in that state, and then injecting an electrolyte that will become a charge transfer layer. Examples of electrolyte injection methods include a method in which two through-holes are provided in the counter electrode, one of which is used as an injection hole and the other as a vent hole, and the electrolyte is injected using capillary action, as described in Patent Document 1, and a method in which one through-hole is provided in the counter electrode, the through-hole is immersed in the electrolyte under reduced pressure, and the electrolyte is injected at atmospheric pressure after being released to the atmosphere, as described in Patent Document 2. However, these electrolyte injection methods have a problem that the tact time (time required for the injection process) of the injection process becomes significantly longer as the area of the battery to be produced increases, and productivity is greatly reduced. In addition, an injection hole must be provided in the electrode in advance, and the injection hole must be sealed after the electrolyte is injected, which increases the number of manufacturing steps. In addition, there is a risk that the electrolyte will leak from the sealed injection hole, which may impair durability.
[0005] In order to solve the above problems, Patent Documents 3, 4, 5, etc. disclose a method for manufacturing a dye-sensitized solar cell (electrolyte dropping method) that includes a step of arranging a dam of a sealant on one electrode without interruption so as to surround a semiconductor-containing layer, dropping a predetermined amount of electrolyte inside the dam of the sealant, overlapping the other electrode, forming a cell gap, and then curing the sealant. These manufacturing methods significantly reduce the tact time of the electrolyte injection step, and also reduce the number of manufacturing steps because the steps of providing an injection hole in the electrode and sealing the injection hole are not necessary. Furthermore, since the obtained solar cell does not have a sealed injection hole portion, it is possible to produce a dye-sensitized solar cell with excellent sealing performance.
[0006] In the electrolyte dripping method, the sealant must be cured in a state where the electrolyte containing the redox couple used in the dye-sensitized solar cell is in contact with the uncured sealant, and the sealant must be durable against external environmental temperature and humidity in order to protect the electrolyte in the manufactured cell. Therefore, the selection of the sealant is important for manufacturing a highly reliable dye-sensitized solar cell. If an inappropriate sealant is used, the electrolyte may break the sealant's dam and gush out due to the pressure when forming the cell gap of the dye-sensitized solar cell or the increase in internal pressure when the sealant is cured, and after manufacturing, the sealant may peel off due to softening of the cured sealant when used in a high-temperature and high-humidity environment, expansion of the electrolyte, or a decrease in the adhesive strength of the sealant to the oxide semiconductor electrode, causing the electrolyte to leak from inside the cell or air bubbles to enter from outside the cell, and there is a risk that a dye-sensitized solar cell with satisfactory reliability and performance cannot be obtained.
[0007] In general, in order to bond an organic substance such as a curable compound to an inorganic substance such as an oxide semiconductor electrode, a method is used in which a compound having a functional group such as a hydroxyl group is added to increase the polarity of the curable compound, thereby increasing the adhesive strength by hydrogen bonding, or a method is used in which an organic substance and an inorganic substance are chemically bonded by adding a coupling agent such as a silane coupling agent. However, in the electrolyte dripping method, in order to once seal the relatively polar electrolyte in an uncured state of the sealant and then cure it, it is preferable to make the curable compound low polar, and the coupling agent itself tends to be easily dissolved in the electrolyte, so it has been difficult to achieve both the sealing performance of the electrolyte and the adhesive strength to the oxide semiconductor electrode. Although the electrolyte dripping method, which includes a process in which the uncured sealant and the electrolyte come into contact with each other, is likely to realize a dye-sensitized solar cell with excellent performance and high productivity, there is no satisfactory sealant that can be used in the method, and many problems remain. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2000-348783 A [Patent Document 2] Patent No. 4037618 [Patent Document 3] International Publication No. 2007 / 046499 [Patent Document 4] JP 2007-220608 A [Patent Document 5] JP 2009-283228 A [Non-patent literature]
[0009] [Non-Patent Document 1] Nature, vol. 353, pp. 737-740, 1991 [Non-Patent Document 2] CJ Barbe, F Arendse, P Compt and M. Graetzel J. Am. Ceram. Soc., 80, 12, 3157-71 (1997). Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been made in view of the above problems, and an object of the present invention is to provide a sealant for dye-sensitized solar cells that has excellent electrolyte sealing performance and high-temperature and high-humidity resistance. [Means for solving the problem]
[0011] That is, the present invention relates to the following [1] to [6]. In this application, "(Numerical value 1) to (Numerical value 2)" indicates that the upper and lower limits are included. In addition, a (meth)acrylic group means a methacrylic group and / or an acrylic group, and a (meth)acrylate means a methacrylate and / or an acrylate. [1] A sealant for dye-sensitized solar cells, which has a storage modulus of 750 MPa or more at 60°C and contains (A) a polybutadiene compound having a (meth)acrylic group in the molecule and (C) a photoradical polymerization initiator. [2] 7. The sealant for a dye-sensitized solar cell according to the above item [1], which is used for a dye-sensitized solar cell obtained by a production method including a step of contacting an electrolyte with an uncured sealant. [3] The sealant for dye-sensitized solar cells according to the above item [1] or [2], further comprising (B) a curable compound and / or (D) a (meth)acrylate having a phosphate group. [4] Further, the sealing agent for dye-sensitized solar cells according to the above item [3], wherein the content of the component (A) is 40 to 80 parts by mass per 100 parts by mass of the total amount of the components (A) and (B). [5] The sealant for a dye-sensitized solar cell according to any one of the above items [1] to [4], further comprising (E) an inorganic filler. [6] A solar cell comprising the sealant for a dye-sensitized solar cell according to any one of items [1] to [5] above. Effect of the Invention
[0012] According to the present invention, it is possible to provide a sealant for dye-sensitized solar cells which has excellent electrolyte sealing performance in the produced dye-sensitized solar cell and can improve the durability of the cell. [Brief description of the drawings]
[0013] [Figure 1] 1 is a schematic cross-sectional view of a main portion of a dye-sensitized solar cell of the present invention. [Diagram 2] 1 shows a substrate for adhesion testing used in Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The sealant for dye-sensitized solar cells of the present invention (also simply referred to as "sealant") comprises (A) a polybutadiene compound having a (meth)acrylic group in the molecule and (C) a photoradical polymerization initiator, and has a storage modulus at 60°C of 750 MPa or more, more preferably 850 MPa or more. The upper limit of the storage modulus at 60°C is preferably 1200 MPa or less, more preferably 1000 MPa or less. The storage modulus of the present invention is measured by the method described in the Examples below.
[0015] Since the electrolyte in the dye-sensitized solar cell expands in a high-temperature, high-humidity environment (for example, an environment of 60°C and 90%), the sealant is subjected to a force from inside the cell. However, the sealant of the present invention has a storage modulus of 750 MPa or more at 60°C, and therefore can maintain the shape of the sealant and improve the durability of the cell. Therefore, the dye-sensitized solar cell obtained using the sealant of the present invention can be efficiently manufactured by the electrolyte dripping method, and can maintain its performance not only in the initial state but also after a high-temperature, high-humidity test.
[0016] [(A) Polybutadiene compound having a (meth)acrylic group in the molecule] The sealing agent of the present invention contains, as component (A), a polybutadiene compound having a (meth)acrylic group in the molecule (also simply referred to as "component (A)"). Component (A) has a (meth)acrylic group, and thus has a fast curing performance by photoreaction, and is excellent in sealing performance for electrolyte and low contamination.
[0017] Component (A) can be commercially available as, for example, TEAI-1000 or TE-2000 manufactured by Nippon Soda Co., Ltd. The number average molecular weight of these polybutadiene compounds having a (meth)acrylic group in the molecule is preferably 500 in terms of preventing electrolyte contamination, more preferably 750, and particularly preferably 1000. In addition, the upper limit of the number average molecular weight is preferably 10000, more preferably 8000, and particularly preferably 6000, in terms of handling properties.
[0018] Component (A) may be used alone or in combination of two or more kinds. Component (A) is preferably contained in an amount of 40 to 80 parts by mass, more preferably 50 to 70 parts by mass, per 100 parts by mass of the total amount of component (A) and component (B) described below. By containing 40 parts by mass or more of component (A), excellent low contamination of the electrolyte can be achieved, and by containing 80 parts by mass or less, performance can be improved by blending with other components.
[0019] [(B) Curable compound] The sealing agent of the present invention contains a curable compound (also simply referred to as "component (B)") as component (B). Component (B) is not particularly limited as long as it is a compound that is cured by light, heat, or the like, but is preferably a compound having a (meth)acrylic group or an epoxy group, and is particularly preferably a compound having a (meth)acrylic group, such as (meth)acrylate, epoxy (meth)acrylate, urethane (meth)acrylate, etc. In the present invention, component (A) and component (D) described below are not included in component (B).
[0020] [(Meth)acrylate] Specific examples of (meth)acrylates include N-acryloyloxyethylhexahydrophthalimide, acryloylmorpholine, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, cyclohexane-1,4-dimethanol mono(meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate, phenylpolyethoxy (meth)acrylate, 2-hydroxy-3-phenyloxypropyl (meth)acrylate, o-phenylphenol monoethoxy (meth)acrylate, and the like. Acrylate, o-phenylphenol polyethoxy (meth)acrylate, p-cumylphenoxyethyl (meth)acrylate, isobornyl (meth)acrylate, tribromophenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, tricyclodecane dimethacrylate, ethanol (meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, bisphenol A polyethoxy di(meth)acrylate, bisphenol A polypropoxy di(meth)acrylate, bisphenol F polyethoxy di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tris(acryloxyethyl)isocyanurate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol Examples of monomers that can be used include penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol penta(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane polyethoxy tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, an ester diacrylate of neopentyl glycol and hydroxypivalic acid, and an ε-caprolactone adduct diacrylate of an ester of neopentyl glycol and hydroxypivalic acid.Preferred examples include isobornyl(meth)acrylate and tricyclodecane dimethanol di(meth)acrylate.
[0021] [Epoxy (meth)acrylate] Epoxy (meth)acrylate is obtained by a known method by reacting epoxy resin with (meth)acrylic acid. The epoxy resin as a raw material is not particularly limited, but is preferably a bifunctional or higher epoxy resin, such as resorcinol diglycidyl ether, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A novolac type epoxy resin, bisphenol F novolac type epoxy resin, alicyclic epoxy resin, aliphatic chain epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, hydantoin type epoxy resin, isocyanurate type epoxy resin, phenol novolac type epoxy resin having a triphenolmethane skeleton, diglycidyl ether of bifunctional phenols such as catechol and resorcinol, diglycidyl ether of bifunctional alcohols, and their halides and hydrogenated products. Bisphenol A type epoxy resin and resorcinol diglycidyl ether are preferably used. In addition, the ratio of epoxy groups to (meth)acryloyl groups is not limited and is appropriately selected from the viewpoint of process compatibility, and may be a partial (meth)acrylate having both epoxy groups and (meth)acryloyl groups.
[0022] Component (B) may be used alone or in combination of two or more kinds. In the sealing agent of the present invention, component (B) is preferably contained in an amount of 20 to 60 parts by mass, more preferably 30 to 50 parts by mass, per 100 parts by mass of the total amount of components (A) and (B).
[0023] The content of the compound having a (meth)acrylic group in 100 parts by mass of the total amount of component (B) is preferably 80 to 100 parts by mass, and particularly preferably 100 parts by mass.
[0024] [(C) Photoradical polymerization initiator] The sealing agent of the present invention may contain a photoradical polymerization initiator (also simply referred to as "component (C)") as component (C). The photoradical polymerization initiator is not particularly limited as long as it is a compound that generates radicals or acids and initiates a chain polymerization reaction when irradiated with ultraviolet light or visible light, and examples of the photoradical polymerization initiator include benzyl dimethyl ketal, 1-hydroxycyclohexyl phenyl ketone, diethylthioxanthone, benzophenone, 2-ethylanthraquinone, 2-hydroxy-2-methylpropiophenone, 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-propane, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, camphorquinone, 9-fluorenone, and diphenyl disulfide. Specifically, IRGACURE RTM 651, 184, 2959, 127, 907, 369, 379EG, 819, 784, 754, 500, OXE01, OXE02, OXE03, OXE04, DAROCURE RTM 1173, LUCIRIN RTM TPO (both manufactured by BASF), Seikuol RTM Z, BZ, BEE, BIP, BBI (all manufactured by Seiko Chemical Co., Ltd.), etc. Among these, preferred is IRGACURE, an oxime ester initiator. RTM OXE01, OXE02, OXE03, OXE04.
[0025] In the sealing agent of the present invention, the component (C) is contained in an amount of preferably 0.001 to 3 parts by mass, and more preferably 0.002 to 2 parts by mass, per 100 parts by mass of the total amount of the sealing agent.
[0026] [(D) (Meth)acrylate having a phosphoric acid group] The sealant of the present invention may contain a (meth)acrylate having a phosphate group as component (D) (also simply referred to as "component (D)"). Component (D) is a compound containing one or more, preferably 1 to 5, phosphate groups and one or more, preferably 1 to 3 (meth)acryloyl groups in one molecule. The mass ratio of component (D) in the sealant for dye-sensitized solar cells of the present invention is usually 0.0005 to 3 mass%, preferably 0.001 to 2 mass%, and more preferably 0.002 to 1 mass%. If it is more than 3 mass%, the transparency of the cured product of the adhesive composition may be deteriorated, and if it is less than 0.0005 mass%, sufficient adhesion cannot be obtained. Component (D) can be used alone or in combination of two or more kinds. In the present invention, by incorporating component (D), the phosphate group bonds with an oxide such as ITO (indium-doped tin oxide) and the acrylate group bonds with a curable resin, which makes it possible to increase the adhesive strength between the sealant and the oxide semiconductor electrode, and prevents peeling of the sealant even under high-temperature and high-humidity conditions, making it possible to retain the electrolyte in the cell.
[0027] The component (D) in the sealant for dye-sensitized solar cells of the present invention is not particularly limited, and examples thereof include 2-(meth)acryloyloxyethyl acid phosphate (e.g., "Light Ester P-1M" and "Light Acrylate P-1A" manufactured by Kyoeisha Chemical Co., Ltd.), alkylene (meth)acrylate phosphates such as methylene (meth)acrylate phosphate, ethylene (meth)acrylate phosphate, propylene (meth)acrylate phosphate, and tetramethylene (meth)acrylate phosphate, phosphate esters of polyethylene glycol monoacrylate, phosphate esters of polypropylene glycol monomethacrylate, bis(2-(meth)acryloyloxyethyl) acid phosphate (e.g., "Light Ester P-2M" and "Light Acrylate P-2A" manufactured by Kyoeisha Chemical Co., Ltd.), ethylene oxide-modified di(meth)acrylate phosphate, and tris(2-acryloyloxyethyl) phosphate, a mixture of caprolactone-modified mono(meth)acrylate phosphate and caprolactone-modified di(meth)acrylate phosphate (for example, "KAYAMER PM-21" manufactured by Nippon Kayaku Co., Ltd.), and the like.
[0028] [(E) Inorganic filler] The sealing agent of the present invention may contain an inorganic filler (also simply referred to as "component (E)") as component (E). Examples of component (E) include silica, silicon carbide, silicon nitride, boron nitride, calcium carbonate, magnesium carbonate, barium sulfate, calcium sulfate, mica, talc, clay, alumina, magnesium oxide, zirconium oxide, aluminum hydroxide, magnesium hydroxide, calcium silicate, aluminum silicate, lithium aluminum silicate, zirconium silicate, barium titanate, glass fiber, carbon fiber, molybdenum disulfide, asbestos, etc., and preferably fused silica, crystalline silica, silicon nitride, boron nitride, calcium carbonate, barium sulfate, calcium sulfate, mica, talc, clay, alumina, aluminum hydroxide, calcium silicate, and aluminum silicate, but preferably silica, alumina, and talc. Two or more of these inorganic fillers may be mixed and used.
[0029] When the component (E) is used in the sealant of the present invention, it is preferably contained in an amount of 5 to 60 parts by mass, more preferably 5 to 50 parts by mass, based on 100 parts by mass of the total amount of the sealant. If the content of the inorganic filler is less than 5 parts by mass, the adhesive strength to the glass substrate decreases, and the moisture resistance reliability is also poor, so that the adhesive strength after moisture absorption may also decrease significantly. If the content of the inorganic filler is more than 60 parts by mass, the filler content is too high, which may cause problems in forming a gap when bonding two electrodes together during the production of a dye-sensitized solar cell.
[0030] [Silane coupling agents] The sealing agent of the present invention may contain a silane coupling agent. Examples of the silane coupling agent include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, N-(2-aminoethyl)3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)3-aminopropylmethyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, vinyltrimethoxysilane, N-(2-(vinylbenzylamino)ethyl)3-aminopropyltrimethoxysilane hydrochloride, 3-methacryloxypropyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, and 3-chloropropyltrimethoxysilane. These silane coupling agents are sold by Shin-Etsu Chemical Co., Ltd. and others as the KBM series and KBE series, and are therefore easily available on the market. When a silane coupling agent is used in the sealing agent of the present invention, it is preferable that the amount of the silane coupling agent is 0.05 to 3 parts by mass per 100 parts by mass of the total amount of the sealing agent.
[0031] [Compounds containing thiol groups] The sealing agent of the present invention may contain a compound having a thiol group. Examples of the compound having a thiol group include methanedithiol, 1,2-dimercaptoethane, 1,2-dimercaptopropane, 2,2-dimercaptopropane, 1,3-dimercaptopropane, 1,2,3-trimercaptopropane, 1,4-dimercaptobutane, 1,6-dimercaptohexane, bis(2-mercaptoethyl)sulfide, 1,2-bis(2-mercaptoethylthio)ethane, 1,5-dimercapto-3-oxapentane, 1,8-dimercapto-3,6-dioxapentane, and the like. saoctane, 2,2-dimethylpropane-1,3-dithiol, 3,4-dimethoxybutane-1,2-dithiol, 2-mercaptomethyl-1,3-dimercaptopropane, 2-mercaptomethyl-1,4-dimercaptobutane, 2-(2-mercaptoethylthio)-1,3-dimercaptopropane, 1,2-bis(2-mercaptoethylthio)-3-mercaptopropane, 1,1,1-tris(mercaptomethyl)propane, tetrakis(mercaptomethyl)methane, ethylene glycol Lithium glycerol bis(2-mercaptoacetate), ethylene glycol bis(3-mercaptopropionate), 1,4-butanediol bis(2-mercaptoacetate), 1,4-butanediol bis(3-mercaptopropionate), trimethylolpropane tris(2-mercaptoacetate), trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(2-mercaptoacetate), pentaerythritol tetrakis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), dipentaerythritol hexakis(2-mercaptoacetate), 1,2-dimercaptobenzene, 1,3-dimercapto-2-propanol, 2,3-dimercapto-1-propanol, 1,2-dimercapto-1,3-butanediol, hydroxyethyl-tris(mercaptoethylthiomethyl)methane, hydroxyethylthiomethyl-tris(mercaptoethylthio)methane, ethylene glycol bis(3-mercaptopropionate), propylene glycol bis(3-mercaptopropionate), butanediol bis(3-mercaptopropionate), octanediol bis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), Ethylene glycol bis(4-mercaptobutyrate), propylene glycol bis(4-mercaptobutyrate), butanediol bis(4-mercaptobutyrate), octanediol bis(4-mercaptobutyrate), trimethylolpropane tris(4-mercaptobutyrate), pentaerythritol tetrakis(4-mercaptobutyrate), ethylene glycol bis(6-mercaptovalerate), propylene glycol bis(6-mercaptovalerate) , butanediol bis(6-mercaptovalerate), octanediol bis(6-mercaptovalerate), trimethylolpropane tris(6-mercaptovalerate), pentaerythritol tetrakis(6-mercaptovalerate), 1,6-hexanedithiol, 1,9-nonanedithiol, 1,10-decanedithiol, 4,4'-bis(mercaptomethyl)phenyl sulfide, 2,4'-bis(mercaptomethyl)phenyl sulfide, 2,4,4'-tri( mercaptomethyl)phenyl sulfide, 2,2',4,4'-tetra(mercaptomethyl)phenyl sulfide, 1,3,5-tris[2-(3-mercaptopropionyloxy)ethyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, pentaerythritol tetrakis(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, polysulfide polymers, etc., which may be used alone or in combination of two or more. Among these, preferred are trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), 1,3,5-tris[2-(3-mercaptopropionyloxy)ethyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris(3-mercapto butyloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and pentaerythritol tetrakis(3-mercaptobutyrate) are preferred, and 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and pentaerythritol tetrakis(3-mercaptobutyrate), which have a secondary thiol structure, are particularly preferred.
[0032] The compound having a thiol group may be produced by a known method, or a commercially available compound may be used. RTM PE1, BD1, NR1, trimethylolpropane tris(3-mercaptobutyrate), trimethylolethane tris(3-mercaptobutyrate) (all manufactured by Resonac), polythiol RTM 340M (manufactured by Toray Fine Chemicals Co., Ltd.), and pentaerythritol tetrakis(3-mercaptopropionate) (manufactured by SC Organic Chemicals Co., Ltd.).
[0033] Also, it is preferable that the compound has three or more functional thiol groups in the molecule. For example, 2,4,4'-tri(mercaptomethyl)phenyl sulfide, 2,2',4,4'-tetra(mercaptomethyl)phenyl sulfide, 1,3,5-tris[2-(3-mercaptopropionyloxy)ethyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, pentaerythritol tetrakis(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, etc. can be mentioned. This is because the heat resistance can be improved by improving the crosslink density.
[0034] When a compound having a thiol group is used in the sealing agent of the present invention, it is preferable that the compound is contained in an amount of 1 to 10 parts by mass per 100 parts by mass of the total amount of the sealing agent.
[0035] [Organic filler] The sealing agent of the present invention may contain an organic filler. Examples of the organic filler include urethane fine particles, acrylic fine particles, styrene fine particles, styrene olefin fine particles, and silicone fine particles. Examples of silicone fine particles include KMP-594, KMP-597, KMP-598 (manufactured by Shin-Etsu Chemical Co., Ltd.), Trefil RTM E-5500, 9701, and EP-2001 (manufactured by Toray Dow Corning Co., Ltd.) are preferred, urethane fine particles are JB-800T and HB-800BK (manufactured by Negami Chemical Industries Co., Ltd.), and styrene fine particles are Rabalon. RTM T320C, T331C, SJ4400, SJ5400, SJ6400, SJ4300C, SJ5300C, and SJ6300C (manufactured by Mitsubishi Chemical Corporation) are preferred, and Septon is a styrene olefin fine particle. RTM SEPS2004 and SEPS2063 are preferred. These organic fillers may be used alone or in combination of two or more. Also, two or more may be used to form a core-shell structure. Among these, acrylic fine particles and silicone fine particles are preferred.
[0036] [Thermal radical polymerization initiator] The sealing agent of the present invention contains a thermal radical polymerization initiator, which can improve the curing speed and curing properties. The thermal radical polymerization initiator is not particularly limited as long as it is a compound that generates radicals by heating and initiates a chain polymerization reaction. Examples of the thermal radical polymerization initiator include organic peroxides, azo compounds, benzoin compounds, benzoin ether compounds, acetophenone compounds, and benzopinacol. Benzopinacol is preferably used. For example, an organic peroxide is KAYAMEK. RTM A, M, R, L, LH, SP-30C, Perkadox CH-50L, BC-FF, Kadox B-40ES, Perkadox 14, Trigonox RTM 22-70E, 23-C70, 121, 121-50E, 121-LS50E, 21-LS50E, 42, 42LS, Kayaester RTM P-70, TMPO-70, CND-C70, OO-50E, AN, Kayabutyl RTM B, Percadox 16, Kayacarvone RTM BIC-75, AIC-75 (manufactured by Kayaku Akzo Co., Ltd.), Permec RTM N, H, S, F, D, G, Perhexa RTM H,HC,TMH,C,V,22,MC,Percure RTM AH, AL, HB, Perbutyl RTM H, C, N.D., L, Park Mill RTM H.D. Perloyle RTM IB, IPP, Perocta RTM ND (manufactured by NOF Corporation) and other products are available commercially.
[0037] In addition, as azo compounds, VA-044, 086, V-070, VPE-0201, VSP-1001 (manufactured by Wako Pure Chemical Industries, Ltd.), and the like are commercially available products.
[0038] The content of the thermal radical polymerization initiator is preferably 0.0001 to 10 parts by mass, more preferably 0.0005 to 5 parts by mass, and particularly preferably 0.001 to 3 parts by mass, per 100 parts by mass of the total amount of the sealing agent of the present invention.
[0039] The sealing agent of the present invention may further contain additives such as a radical polymerization inhibitor, a pigment, a leveling agent, a defoaming agent, a solvent, etc. These additives are preferably ones that have low staining properties for the charge transport layer.
[0040] [Radical polymerization inhibitors] The radical polymerization inhibitor is not particularly limited as long as it is a compound that reacts with radicals generated from a photoradical polymerization initiator or a thermal radical polymerization initiator to prevent polymerization, and may be a quinone, piperidine, hindered phenol, nitroso, etc. Specifically, naphthoquinone, 2-hydroxynaphthoquinone, 2-methylnaphthoquinone, 2-methoxynaphthoquinone, 2,2,6,6-tetramethylpiperidine-1-oxyl, 2,2,6,6-tetramethyl-4-hydroxypiperidine-1-oxyl, 2,2,6,6-tetramethyl-4-methoxypiperidine-1-oxyl, 2,2,6,6-tetramethyl-4-phenoxypiperidine-1-oxyl, or hydroquinone. , 2-methylhydroquinone, 2-methoxyhydroquinone, parabenzoquinone, butylated hydroxyanisole, 2,6-di-t-butyl-4-ethylphenol, 2,6-di-t-butylcresol, stearyl β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 4,4'-thiobis(3-methyl-6-t-butylpheno 4,4'-butylidenebis(3-methyl-6-t-butylphenol), 3,9-bis[1,1-dimethyl-2-[β-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl], 2,4,8,10-tetraoxaspiro[5,5]undecane, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenylpropionate)methane], 1,3,5-trimethylphenylpropionate, Examples of the aluminum salt of tris(3',5'-di-t-butyl-4'-hydroxybenzyl)-sec-triazine-2,4,6-(1H,3H,5H)trione, paramethoxyphenol, 4-methoxy-1-naphthol, thiodiphenylamine, N-nitrosophenylhydroxyamine, trade names Adeka STAB LA-81 and Adeka STAB LA-82 (manufactured by Adeka Corporation), but are not limited to these.Among these, naphthoquinone-based, hydroquinone-based, nitroso-based, and piperazine-based radical polymerization inhibitors are preferred, naphthoquinone, 2-hydroxynaphthoquinone, hydroquinone, 2,6-di-tert-butyl-p-cresol, and Polystop 7300P (manufactured by Hakuto Co., Ltd.) are more preferred, and Polystop 7300P (manufactured by Hakuto Co., Ltd.) is most preferred.
[0041] The content of the radical polymerization inhibitor is preferably 0.0001 to 1 part by mass, more preferably 0.001 to 0.5 parts by mass, and particularly preferably 0.01 to 0.2 parts by mass, per 100 parts by mass of the total amount of the sealing agent of the present invention.
[0042] The following method is one example of a method for obtaining the sealing agent of the present invention. First, components (A), (B), and (C) are heated and dissolved. After cooling to room temperature, component (D) is added, and if necessary, component (E), a silane coupling agent, a compound having a thiol group, an antifoaming agent, a leveling agent, a solvent, etc. are added, and the mixture is mixed uniformly using a known mixing device such as a three-roll mill, a sand mill, a ball mill, a planetary mixer, etc., to produce the sealing agent. If necessary, a filtration process may be performed after mixing to remove impurities.
[0043] A solar cell manufactured using the sealing agent of the present invention will be described in detail below. The following specific embodiments are merely examples, and the present invention is not limited thereto.
[0044] In general, a dye-sensitized solar cell is composed of a first conductive support (oxide semiconductor electrode) having a semiconductor-containing layer sensitized with a dye on its surface, a second conductive support as a counter electrode, and a charge transfer layer as its main components. The sealant of the present invention is used for the purpose of bonding the first and second conductive supports and holding the charge transfer layer between the two supports. As the conductive support, for example, a conductive material represented by FTO (fluorine-doped tin oxide), ATO (antimony-doped tin oxide), and ITO (indium-doped tin oxide) is formed into a thin film on the surface of a substrate such as glass, plastic, polymer film, quartz, or silicon. The thickness of the substrate is usually 0.01 to 10 mm, and the shape can be various from a film to a plate, but at least one of the two substrates is a light-transmitting substrate. The conductivity of the conductive support is usually 1000 Ω / cm 2 Less than 100Ω / cm, preferably 2 The following is the result.
[0045] As the oxide semiconductor used in the preparation of the semiconductor-containing layer, fine particles of metal chalkenide are preferred. Specific examples thereof include oxides of transition metals such as Ti, Zn, Sn, Nb, W, In, Zr, Y, La, and Ta, oxides of Al, oxides of Si, and perovskite-type oxides such as SiTiO3, CaTiO3, and BaTiO3. Among these, TiO2, ZnO, and SnO2 are particularly preferred. These may also be used in a mixture, and a preferred example is a SnO2-ZnO mixture. In the case of a mixture, the components may be mixed in the form of fine particles, or in the form of a slurry or paste as described below, or each component may be layered. The concentration of the oxide semiconductor in the slurry or paste is usually 1 to 90% by mass, preferably 5 to 80% by mass. The primary particle size of the oxide semiconductor used is usually 1 to 200 nm, preferably 1 to 50 nm.
[0046] Methods for preparing the semiconductor-containing layer include a method of forming a thin film made of an oxide semiconductor directly on a substrate by vapor deposition, a method of forming the layer by applying or coating a slurry or paste onto a substrate and then applying pressure, a method of electrically depositing the layer using the substrate as an electrode, a method of applying or coating a slurry or paste onto a substrate and then drying, curing or baking the layer, etc. Examples of the application or coating method include a bar coater method, a dip coating method, a spin coating method, a spray method, a screen printing method, a doctor blade method, a dispense method, etc.
[0047] These methods can be appropriately selected or used in combination depending on the type and form of the substrate. In terms of the performance of the oxide semiconductor electrode, a method using a slurry or paste is preferred. The slurry can be obtained, for example, by dispersing secondary aggregated oxide semiconductor particles in a dispersion medium using a dispersant so that the average primary particle size is usually 1 to 200 nm, or by hydrolyzing an alkoxide, which is a precursor of the oxide semiconductor, by a sol-gel method. Furthermore, oxide semiconductor particles having different particle size distributions may be mixed and used.
[0048] The dispersion medium for dispersing the slurry is not particularly limited as long as it can disperse oxide semiconductor particles. As the dispersion medium, organic solvents such as water, alcohols such as ethanol and terpineol, ketones such as acetone and acetylacetone, and hydrocarbons such as hexane are used. These may be used in combination. The use of water is preferable in terms of reducing the change in viscosity of the slurry. In order to obtain stable primary particles, a dispersion stabilizer or the like may be added to the slurry. Specific examples of the dispersion stabilizer used include polyhydric alcohols such as polyethylene glycol, phenol, octyl alcohol, and other monohydric alcohols, or their mutual co-condensates; cellulose derivatives such as hydroxypropylmethylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, and carboxymethylcellulose; polyacrylamide; acrylamide, (meth)acrylic acid or its salt, (meth)acrylic acid ester (methyl (meth)acrylate, ethyl (meth)acrylate, etc.), or other mutual co-condensates; water-soluble polyacrylic acid derivatives which are copolymers of acrylamide, (meth)acrylic acid or its salt, (meth)acrylic acid ester, etc. with hydrophobic monomers such as styrene, ethylene, and propylene; salts of melamine sulfonic acid formaldehyde condensates; salts of naphthalene sulfonic acid formaldehyde condensates; high molecular weight lignin sulfonates; acids such as hydrochloric acid, nitric acid, and acetic acid, but are not limited thereto. In addition, these dispersion stabilizers may be used alone, or two or more of them may be used in combination.
[0049] Among these, preferred are polyhydric alcohols such as polyethylene glycol, self- or mutual co-condensates of phenol, octyl alcohol, etc., poly(meth)acrylic acid, sodium poly(meth)acrylate, potassium poly(meth)acrylate, lithium poly(meth)acrylate, carboxymethylcellulose, hydrochloric acid, nitric acid, acetic acid, etc.
[0050] After drying the slurry applied onto the conductive support, a firing treatment can be carried out at a temperature equal to or lower than the melting point (or softening point) of the substrate used for the conductive support. The firing temperature is usually 100 to 900°C, preferably 100 to 600°C. The firing time is not particularly limited, but is generally within 4 hours. The thickness of the semiconductor-containing layer provided on the conductive support is usually 1 to 50 μm.
[0051] For the purpose of improving the surface smoothness, the semiconductor-containing layer may be subjected to a secondary treatment (see Non-Patent Document 2). For example, the smoothness of the semiconductor-containing layer can be improved by directly immersing the conductive support provided with the thin film of the semiconductor-containing layer prepared by the above-mentioned method in a solution of alkoxide, chloride, nitrate, sulfide, or the like of the same metal used in the preparation of the semiconductor-containing layer, and drying the conductive support, or by optionally further baking (re-baking) in the same manner as above. Here, examples of the metal alkoxide include titanium ethoxide, titanium isopropoxide, titanium t-butoxide, n-dibutyl-diacetyltin, and the like, and alcohol solutions thereof are used. In the case of chlorides, examples of the metal alkoxides include titanium tetrachloride, tin tetrachloride, zinc chloride, and the like, and aqueous solutions thereof are used. The specific surface area of the semiconductor-containing layer made of oxide semiconductor fine particles obtained in this manner is usually 1 to 1000 m 2 / g, preferably 10 to 500m 2 / g.
[0052] Next, the process of supporting a sensitizing dye on the semiconductor-containing layer will be described. The sensitizing dye is not particularly limited as long as it has the effect of sensitizing light absorption together with the semiconductor fine particles constituting the semiconductor-containing layer. As the sensitizing dye, a metal complex dye containing a metal element such as ruthenium or an organic dye not containing a metal may be used alone, or several types may be mixed in any ratio. When used in a mixed state, it may be a combination of multiple types of metal complex dyes, multiple types of organic dyes, or a combination of a metal complex dye and an organic dye. By mixing multiple types of dyes with different absorption wavelength ranges, a wide range of absorption wavelengths can be used, and a solar cell with high conversion efficiency can be obtained.
[0053] There is no particular limit to the metal complex dye that can be supported, but phthalocyanine, porphyrin, etc. are preferred, and ruthenium complexes are more preferred. There is also no particular limit to the organic dye that can be supported, and examples thereof include metal-free phthalocyanine, porphyrin, cyanine, merocyanine, oxonol, triphenylmethane-based, acrylic acid-based dyes, methine dyes such as pyrazolone-based methine dyes, and xanthene-based, azo-based, anthraquinone-based, and perylene-based dyes. International Publication No. 2002-001667, International Publication No. 2002-011213, International Publication No. 2002-071530, JP 2002-334729 A, JP 2003-007358 A, JP 2003-017146 A, JP 2003-059547 A, JP 2003-086257 A, JP 2003-115333 A, JP 2003-132965 A, JP 2003-142172 A, JP 2003-151649 A, JP 2003- It is preferable to use dyes described in JP-A-157915, JP-A-2003-282165, JP-A-2004-014175, JP-A-2004-022222, JP-A-2004-022387, JP-A-2004-227825, JP-A-2005-005026, JP-A-2005-019130, JP-A-2005-135656, JP-A-2006-079898, JP-A-2006-134649, International Publication No. 2006-082061, etc. It is more preferable to use methine dyes such as merocyanine and the above-mentioned acrylic acid-based dyes. When a mixture of multiple dyes is used, the ratio of each dye is not particularly limited, but it is generally preferable to use at least about 10 mol% of each dye. When a solution in which two or more dyes are dissolved or a dispersion in which two or more dyes are dispersed is used to support the dye in the semiconductor-containing layer, the total concentration of the dye in the solution may be the same as when only one type is supported. When a mixture of multiple dyes is used, the solvents described above for the oxide semiconductor can be used, and the solvents used for each dye may be the same or different.
[0054] The method of supporting the sensitizing dye includes a method of immersing the conductive support provided with the semiconductor-containing layer in a solution in which the dye is dissolved in a solvent or a dispersion in which the dye is dispersed in a solvent. The concentration of the dye in the solution or dispersion may be appropriately determined depending on the type and solubility of the dye. The immersion temperature is generally from room temperature to the boiling point of the solvent, and the immersion time may be about 1 hour to 72 hours. Specific examples of solvents that can be used to dissolve the sensitizing dye include methanol, ethanol, acetone, acetonitrile, dimethyl sulfoxide, dimethylformamide, t-butanol, tetrahydrofuran, etc. These may be used alone or in a mixture of two or more in any ratio. The concentration of the sensitizing dye in the solution is usually 1×10 -6 M to 1M, preferably 1×10 -5 M~1×10 -1 In this way, a conductive support having a dye-sensitized semiconductor-containing layer is obtained, which is used as an oxide semiconductor electrode.
[0055] When the dye is supported on the semiconductor-containing layer, it is effective to support the dye in the presence of an inclusion compound in order to prevent the dye particles from associating. Examples of the inclusion compound include steroid compounds such as cholic acid, crown ethers, cyclodextrins, calixarene, and polyethylene oxide. Preferred examples include cholic acids such as cholic acid, deoxycholic acid, chenodeoxycholic acid, cholic acid methyl ester, sodium cholate, and ursodeoxycholic acid, and polyethylene oxide. The inclusion compounds may be used in the form of being added to a dye solution, or the inclusion compounds may be dissolved in a solvent in advance and then the dye may be dissolved or dispersed. Two or more of these inclusion compounds may be used in combination, and the ratio may be selected arbitrarily. After the dye is supported, the semiconductor-containing layer may be treated with an amine compound such as 4-t-butylpyridine. The treatment method may be, for example, a method of immersing the conductive support provided with the semiconductor-containing layer supported with the dye in an ethanol solution of an amine compound.
[0056] The counter electrode is made by evaporating conductive fine particles of platinum, carbon, rhodium, ruthenium, etc., which act catalytically in the reduction reaction of the redox electrolyte, onto the surface of a conductive support such as FTO conductive glass, or by coating and baking the precursors of these conductive fine particles on the surface.
[0057] Next, the charge transfer layer will be described. For the charge transfer layer, a solution in which a redox electrolyte pair and a hole transport material are dissolved in a solvent or a room temperature molten salt (ionic liquid) is used. Examples of the redox electrolyte used include a halogen redox electrolyte consisting of a halogen compound and a halogen molecule with a halogen ion as a counter ion, a metal redox electrolyte such as a metal complex such as a ferrocyanide salt-ferricyanide salt, a ferrocene-ferricinium ion, and a cobalt complex, and an organic redox electrolyte such as an alkylthiol-alkyl disulfide, a viologen dye, and hydroquinone-quinone. A halogen redox electrolyte is preferred. Examples of the halogen molecule in the halogen redox electrolyte include an iodine molecule and a bromine molecule, and an iodine molecule is preferred. Examples of halogen compounds include metal halide salts such as LiI, NaI, KI, CsI, CaI2, and CuI, and organic quaternary ammonium salts of halogen such as tetraalkylammonium iodide, imidazolium iodide, 1-methyl-3-alkylimidazolium iodide, and pyridinium iodide. Salt compounds with iodide ions as counter ions are preferred. Specific examples of such salts include lithium iodide, sodium iodide, and trimethylammonium iodide salts. These may be used alone or in combination of two or more.
[0058] In addition, when the charge transfer layer is composed of a solution containing an oxidation-reduction electrolyte, an electrochemically inactive solvent is used. Specific examples of the solvent used include acetonitrile, valeronitrile, propylene carbonate, ethylene carbonate, 3-methoxypropionitrile, 3-butoxypropionitrile, methoxyacetonitrile, ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, dimethoxyethane, diethyl carbonate, diethyl ether, dimethyl carbonate, 1,2-dimethoxyethane, dimethylformamide, dimethyl sulfoxide, 1,3-dioxolane, methyl formate, 2-methyltetrahydrofuran, 3-methyloxazolidin-2-one, γ-butyrolactone, sulfolane, tetrahydrofuran, and water. Among these, acetonitrile, propylene carbonate, ethylene carbonate, 3-methoxypropionitrile, methoxyacetonitrile, ethylene glycol, 3-methyloxazolidin-2-one, γ-butyrolactone, and the like are preferred. These may be used alone or in combination of two or more. The concentration of the redox electrolyte in the solution is usually 0.01 to 99% by mass, preferably 0.1 to 90% by mass.
[0059] In addition, when the charge transfer layer is configured in the form of a composition containing a redox electrolyte, a room temperature melt (ionic liquid) is used as a solvent. Specific examples of room temperature melts that can be used include 1-methyl-3-alkylimidazolium iodide, vinylimidazolium tetrafluoride, 1-ethylimidazole sulfonate, alkylimidazolium trifluoromethylsulfonylimide, 1-methylpyrrolidinium iodide, and the like. In addition, for the purpose of improving the durability of the dye-sensitized solar cell, for example, a gel electrolyte can be obtained by dissolving a low molecular weight gelling agent in the charge transfer layer to thicken it, or by injecting a charge transfer layer containing a reactive component and then reacting it to gel it, or by impregnating the charge transfer layer with a gel that has been polymerized in advance.
[0060] On the other hand, in the case of a completely solid-state charge transfer layer, a hole transport material or a P-type semiconductor can be used instead of the redox electrolyte. Examples of hole transport materials that can be used include amine derivatives and conductive polymers such as polyacetylene, polyaniline, and polythiophene. Examples of P-type semiconductors include CuI and CuSCN.
[0061] A dye-sensitized solar cell can be obtained by injecting a charge transfer layer into the gap between a pair of conductive supports and then sealing the injection port of the charge transfer layer. As a sealant (sealing agent) for sealing the injection port of the charge transfer layer, isobutylene resin, epoxy resin, UV-curable acrylic resin, etc. can be used.
[0062] Next, a method for producing a dye-sensitized solar cell using the sealant of the present invention will be described. After adding a spacer (gap control material) such as glass fiber to the sealant of the present invention, the sealant is applied to one of the pair of substrates using a dispenser or a screen printing device, etc., and a seamless dam is provided so as to surround the semiconductor-containing layer. Then, a charge transfer layer that becomes a charge transfer layer is dropped on the inside of the dam of the sealant using a dispenser or the like. At that time, the amount of the charge transfer layer dropped is adjusted so that the gap between the electrodes after the electrodes are bonded to a predetermined size. The type of the charge transfer layer to be enclosed is not particularly limited. The amount of the charge transfer layer dropped can be calculated from the effective area and cell gap of the solar cell. Then, the first and second conductive supports are placed in a vacuum bonding device so as to face each other, and the two electrodes are overlapped under reduced pressure, and the pressure is returned to atmospheric pressure to form a gap. After the gap is formed, the sealant is irradiated with ultraviolet light by an ultraviolet irradiator to photocure it. The amount of ultraviolet light irradiation is preferably 500 to 6000 mJ / cm. 2 , more preferably 1000 to 4000 mJ / cm 2 The preferred irradiation dose is 100 nm (measurement wavelength: 365 nm). Thereafter, if necessary, curing is performed at 60 to 120° C. for 30 minutes to 2 hours to obtain the electrochemical cell of the present invention. The gap (cell gap) between the first and second conductive supports is usually 1 to 100 μm, and preferably 20 to 70 μm.
[0063] Fig. 1 is a schematic cross-sectional view of a main part illustrating the structure of a dye-sensitized solar cell prepared using the sealing agent of the present invention. In the figure, 1 is a conductive support having conductivity on the inside, 2 is a semiconductor-containing layer sensitized by a dye (1 and 2 are collectively referred to as an oxide semiconductor electrode), 3 is a counter electrode in which platinum or the like is disposed on the conductive surface on the inside of the conductive support, 4 is a charge transfer layer disposed in the gap between the pair of conductive supports, 5 is the sealing agent of the present invention, and 6 is a glass substrate. Lead wires are disposed on the positive and negative electrodes of the dye-sensitized solar cell thus obtained, and a resistance component is inserted between them to obtain a solar cell of the present invention.
[0064] The sealant of the present invention can also be applied to the production of a large-area dye-sensitized solar cell module in which a plurality of dye-sensitized solar cells arranged in a plane are electrically connected in series. Several types of module structures for large-area dye-sensitized solar cells are known. The sealant of the present invention can be used for any type of module structure. For example, it can also be used for a dye-sensitized solar cell module having a series connection structure described in International Publication No. 2009 / 057704 and the like.
[0065] The sealant of the present invention is excellent in workability for application to a substrate, lamination property, adhesion property, and sealing performance of an electrolyte solution in a manufacturing process of a dye-sensitized solar cell, and is excellent in adhesive strength to an oxide semiconductor electrode and durability in a high-temperature and high-humidity environment. Therefore, the dye-sensitized solar cell of the present invention obtained by using the sealant can be efficiently manufactured by an electrolyte dropping method and has excellent durability, and can be applied at low cost to a wide range of applications from indoor to outdoor use. EXAMPLES
[0066] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0067] [Examples 1 to 5, Comparative Examples 1 to 6] Components (A), (B), and (C) were heated and mixed at 90°C in the ratios shown in Table 1 below, and then cooled to room temperature. Components (D) and (E) and additives were added and stirred, and then dispersed in a planetary mixer to prepare a sealant.
[0068] [viscosity] 0.15 mL of sealant was added to the measuring cup of an E-type viscometer (RE105 by Toki Sangyo Co., Ltd.). After leaving it for 120 seconds as preheating under conditions of a temperature of 25°C and a cone of 3° x R7.7, the value after 120 seconds at a rotation speed of 5 rpm was measured. The results are shown in Table 1.
[0069] [Thixotropy ratio] 0.15 mL of sealant was added to the measuring cup of an E-type viscometer (RE105, Toki Sangyo Co., Ltd.). After leaving it for 120 seconds as preheating under conditions of 25°C temperature and cone 3° x R7.7, the values after 120 seconds at a rotation speed of 5 rpm and 120 seconds at a rotation speed of 0.5 rpm were measured. The thixotropic ratio was calculated by dividing the viscosity value at 0.5 rpm by the viscosity value at 5 rpm. The results are shown in Table 1.
[0070] [Storage modulus at 60℃] The sealants produced in the examples and comparative examples were sandwiched between polyethylene terephthalate (PET) films to form thin films with a thickness of 100 μm, which were then irradiated with 3000 mJ / cm 2 UV light. 2 After irradiating with ultraviolet light (measurement wavelength: 365 nm), the material was placed in an oven and thermally cured at 80°C for 60 minutes. After curing, the PET film was peeled off to obtain a sample. The prepared sample was cut into a 50 mm x 5 mm strip to obtain a sample piece, and this sample piece was measured using a dynamic viscoelasticity measuring device (DMS-6100: manufactured by SII Nano Technology) in tension mode at a frequency of 10 Hz and a heating rate of 3°C / min. The results are shown in Table 1.
[0071] [Electrolyte sealing performance] A test was carried out to confirm whether the sealant had the ability to seal the electrolyte. Specifically, the test was carried out according to the following description. The sealant produced in the examples and comparative examples was dispensed in a 1 cm x 1 cm cell shape on the ITO film on the glass substrate with ITO so that the line width after lamination would be 1.0 mm, and then minute droplets of electrolyte were dropped within the frame of the seal pattern. Furthermore, an in-plane spacer (Hayabeads SD-BD-DEA-LT 20 μm: manufactured by Hayakawa Rubber Co., Ltd.) was sprayed on the ITO film of another glass substrate with ITO electrode, which was then thermally fixed, and the substrate to which the electrolyte had been dropped was laminated in a vacuum using a lamination device. After opening to the atmosphere to form a gap, the substrate was irradiated with 3000 mJ / cm using a UV irradiator. 2 After irradiating with ultraviolet light (measurement wavelength: 365 nm), the cell was placed in an oven and heated at 80°C for 60 minutes to prepare an electrolyte test cell for evaluation. The obtained evaluation cell was observed under a microscope, and the adhesion state of the sealant was evaluated according to the following criteria. The results are shown in Table 1. ○: The sealant seals the electrolyte, and the electrolyte is not inserted into the sealant. ×: Electrolyte is leaking from the sealant or electrolyte is seeping into the sealant.
[0072] [High temperature and humidity reliability test performance] The 1cm x 1cm electrolyte-sealed cells prepared for the electrolyte sealing performance evaluation were placed in a constant temperature and humidity tester set at 60°C and 90%, and the cells were removed from the tester at regular intervals to visually inspect whether the cells were being maintained. The cells were placed in the high temperature and humidity tester for a maximum of 1000 hours. A state in which the cell was being maintained refers to a state in which the sealant had not peeled off from the ITO-coated glass substrate, there was no leakage of electrolyte to the outside of the cell, and no intrusion of air bubbles from the outside of the cell. An evaluation was performed according to the following criteria, depending on the time the cells were maintained. The results are shown in Table 1. 〇: 1000 hours durability △: Cell collapses within 500 to 1000 hours ×: Cell collapses within 500 hours
[0073] [Oxide semiconductor electrode adhesive strength] The sealants produced in the examples and comparative examples were mixed and stirred with a planetary stirrer (EME: VMX-360) and filled into a 5 ml syringe. The filled sealant was applied onto the ITO film of a 0.5 mm thick glass substrate with an ITO electrode in a shape that reproduced a corner portion with R=0.5 mm and length of 1 cm x 1 cm so that the line width after bonding would be 1.0 mm. Furthermore, an in-plane spacer (Hayabeads SD-BD-DEA-LT 4 μm: Hayakawa Rubber Co., Ltd.) was sprayed onto the ITO film of another glass substrate with an ITO electrode, thermally fixed, and bonded to the previous substrate coated with the sealant in a vacuum using a bonding device. After opening to the atmosphere to form a gap, 3000 mJ / cm was applied using a UV irradiator. 2 After irradiating with ultraviolet light (measurement wavelength: 365 nm), the substrate was placed in an oven and heated at 80°C for 60 minutes. The resulting bonded substrate was cut into a shape in which only the lower substrate protruded as shown in Figure 2, and the lower substrate was pressed at a point 4 mm away diagonally from the corner of the applied display sealant using a universal testing machine (Shimadzu Corporation: Autograph AG-Xplus500N) equipped with a 3 mmφ needle-type terminal, and the maximum load when the bonded substrates peeled off was measured to determine the adhesive strength. The results are shown in Table 1.
[0074] [Table 1]
[0075] [Table 2]
[0076] As can be seen from the results in Table 1, the sealant of the present invention is excellent in electrolyte sealing performance and high temperature and humidity resistance, and therefore can provide a highly reliable dye-sensitized solar cell. [Industrial Applicability]
[0077] The sealant for dye-sensitized solar cells of the present invention is excellent in workability for applying to a substrate, lamination property, adhesion property, and sealing performance of an electrolyte solution, and is extremely low in contamination, in the manufacturing process of the dye-sensitized solar cell. Therefore, the dye-sensitized solar cell of the present invention obtained by using the sealant can be efficiently manufactured by an electrolyte solution dropping method, and has excellent durability. [Explanation of symbols]
[0078] 1. Conductive support 2. Dye-sensitized semiconductor-containing layer 3 Counter electrode 4. Charge transfer layer 5. Sealant 6 Glass substrate
Claims
1. A sealant for dye-sensitized solar cells, which has a storage modulus of 750 MPa or more at 60° C. and contains (A) a polybutadiene compound having a (meth)acrylic group in the molecule and (C) a photoradical polymerization initiator.
2. The sealant for a dye-sensitized solar cell according to claim 1, which is used for a dye-sensitized solar cell obtained by a production method including a step of contacting an electrolyte with an uncured sealant.
3. The sealant for dye-sensitized solar cells according to claim 1 , further comprising (B) a curable compound and / or (D) a (meth)acrylate having a phosphoric acid group.
4. The sealing agent for dye-sensitized solar cells according to claim 3, wherein the content of the component (A) is 40 to 80 parts by mass per 100 parts by mass of the total amount of the components (A) and (B).
5. The sealant for a dye-sensitized solar cell according to claim 3 , further comprising (E) an inorganic filler.
6. A solar cell comprising the sealant for a dye-sensitized solar cell according to claim 1 .
Citation Information
Patent Citations
Manufacture of pigment-sensitized type solar cell
JP2000348783A
Method of manufacturing dye-sensitized solar cell, and dye-sensitized solar cell
JP2007220608A
Method for manufacturing of dye-sensitized solar cell
JP2009283228A
Dye-sensitized solar cell and manufacturing method thereof
JP4037618B2
Dye-sensitized photoelectric conversion device and method for manufacturing same
WO2007046499A1